Production of industrial dextrin from tapioca starch - Martinez, Nancy C.; Versoza, Lyra R.; Pigao, Menandro E.; Villavert, Ricardo T. (College of Engineering, 1999)
Products: White Dextrin, Yellow Dextrin -- Plant location: Bauan, Batangas -- Total land area: 3,000 square meters -- Annual volume of production at full plant capacity: 1,500 metric tons (White Dextrin), 650 metric tons (Yellow Dextrin) -- Annual gross sales: Php 69,111,775.00 -- Annual income: Php 14,167,844.00 -- Total Investment Cost: Php 28,852,326.00 -- working capital: Php 5,444,996.00 -- Product cost: Php 20,652.00/metric ton (White Dextrin), Php 24,014.00/metric ton (Yellow Dextrin) -- Product selling price: Php 30,000.00/metric ton (White Dextrin), Php 35,000.00/metric ton (Yellow Dextrin) -- Return on investment: 49.10% -- Payback period: 1.36 years -- Break-even selling price: Php 23,870/metric ton (White Dextrin), Php 27,850/metric ton (Yellow Dextrin) -- Break-even volume: 998.2 metric tons/year (White Dextrin), 427.8 metric tons/year (Yellow Dextrin)